Правові засади організації та діяльності міліції УРСР у 1949–1950-х рр. - Брусакова, О. В.; Brusakova, O. V.; Греченко, В. А.; Grechenko, V. A.; Оксана Брусакова (Право і безпека. – 2022. – № 2 (85). – С. 121-130, 2022)
Досліджено основні аспекти структури міліції у 1949–1950-х рр., головні напрями її діяльності. Висвітлено зміни у Кримінально-процесуальному кодексі УРСР, якими керувалася міліція при здійсненні своєї правоохоронної функції. Відмічено, що структура місцевих органів міліції по областях України в повоєнний період була однотипною, але могла відрізнятися (залежно від оперативних умов) кількістю штатних одиниць. Проаналізовано причини злочинності у вказаний період. Значну увагу приділено роботі міліції щодо протидії злочинності, яка здійснювалася за такими напрямами: 1) попередження та розкриття злочинів структурними підрозділами міліції (карного розшуку і боротьби з розкраданням соціалістичної власності та спекуляції); 2) проведення дізнання та здійснення низки слідчих функцій.

The main aspects of the structure of the police in 1949–1950 and the main directions of its activity have been studied. The changes in the Criminal Procedure Code of the Ukrainian SSR guided by the police in the performance of their law enforcement functions have been highlighted. It has been noted that the structure of local police bodies in the regions of Ukraine in the post-war period was of the same type, but could differ depending on operational conditions in the number of regular units. The most important change in the structure of the Ministry of Internal Affairs during this period was the transfer of the police to the Ministry of State Security in October 1949. The activities of the police were controlled and regulated by decisions and resolutions of the Communist Party of Ukraine. First of all, it concerned the selection of personnel and education of police personnel. The central governing body of the police was the Main Directorate of the Police. The police departments of the Union republics, regions, large cities, district departments and branches, military units of the police were subordinate to it. At the same time, the heads of these police bodies held the positions of deputy people’s commissars of internal affairs of the republics, heads of regional NKVD (People’s Commissary of Internal Affairs) departments, heads of departments and NKVD departments of cities and districts. The causes of crime in the specified period have been analyzed. Considerable attention has been paid to the work of the police in combating crime, which was carried out in the following areas: 1) prevention and detection of crimes by structural units of the police (criminal investigation and fight against theft of socialist property and speculation); 2) conducting inquiries and performing a number of investigative functions. Factors that did not allow the police to fully perform their functions in the fight against crime were: 1) insufficient use of scientific and technical means; 2) lack of an extensive agent-informant network; 3) lack of professional personnel; 4) violation of “socialist legality” during inquiry and investigation; 5) involvement of operatives of criminal investigation and employees of anti-theft of socialist property and speculation of the BRSVS (the department for combating embezzlement of socialist property and speculation) to perform functions that are not specific to them. The practical activity of police bodies for the protection of public order was determined by the following directions: 1) administrative activity (patrol in populated areas, compliance with the rules of the passport and permit system, regulation of street traffic); 2) involvement of state institutions, public organizations and citizens in cooperation; 3) creation of voluntary formations - police assistance brigades and public order protection groups.

Исследованы основные аспекты структуры милиции в 1949–1950 гг., главные направления ее деятельности. Освещены изменения в Уголовно-процессуальном кодексе УССР, которым руководствовалась милиция при осуществлении своей правоохранительной функции. Отмечено, что структура местных органов милиции по областям Украины в послевоенный период была однотипной, но могла отличаться (в зависимости от оперативных условий) количеством штатных единиц. Проанализированы причины преступности в указанный период. Значительное внимание уделено работе милиции по противодействию преступности, которая осуществлялась по таким направлениям: 1) предупреждение и раскрытие преступлений структурными подразделениями милиции (уголовного розыска и борьбы с хищением социалистической собственности и спекуляции); 2) проведение дознания и воплощение ряда следственных функций.
Legal foundations of the organization and activities of the Ukrainian SSR police in 1949–1950s
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Історія. History. История; Україна. Ukraine. Украина; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; internal affairs agencies; органы внутренних дел; міліція; нормативно-правова база; протидія злочинності; милиция; militia; нормативно-правовая база; regulatory and legal basis; crime prevention; противодействие преступности